Storytelling as a Method for Internalizing Islamic Moral Values in Integrated Early Childhood Education - Agustina, Dena (Sekolah Tinggi Agama Islam Kuningan, 2025)
Backround: The integration of Islamic moral values in early childhood education faces challenges in finding effective pedagogical methods that resonate with young children's developmental characteristics.Objective: This study investigates the effectiveness of storytelling as a method for internalizing Islamic moral values in integrated early childhood education settings.Method: A mixed-methods approach was employed with 120 children aged 5-6 years from three integrated Islamic kindergartens in Indonesia. Data collection involved pre-post moral reasoning assessments, classroom observations, and teacher interviews over 12 weeks. Quantitative data were analyzed using paired t-tests and ANOVA, while qualitative data underwent thematic analysis.Findings and Implications: Children exposed to Islamic storytelling demonstrated significant improvements in moral reasoning scores (M=78.4, SD=8.2) compared to baseline (M=58.6, SD=9.1), t (119) =15.82, p<.001, d=2.31. Thematic analysis revealed three key mechanisms: emotional engagement, character identification, and narrative scaffolding. Conclusion: Storytelling provides a developmentally appropriate and culturally responsive method for moral education, suggesting its integration into Islamic early childhood curricula as a primary pedagogical strategy.